POTRET RELASI GENDER PADA KELUARGA ULUN LAPPUNG (TINJAUAN ETNOLOGI) - Nency Dela Oktora (Center of Gender Studies and Child of State Islamic Institute of Metro, 2019)
This study discusses the roots of different views on the manifestations of gender differences in the patriarchal Ulun Lappung family relationship portrait which dichotomizes the roles of men (husband) and women (wife) in a household shelter, where the husband is the head of the family (public) and the wife is a housewife (domestic). Manifestations of dichotomous family relations patterns, resulting in gender inequality and inequality. Besides patriarchalism, another thing that affects injustice and gender inequality is the environment of people's lives with stronger social interactions by ethnic, religious, and kinship ties with each other having a very dominant cultural system. The existing social structure is still very much influenced by the customs and cultural traditions that are passed down from generation to generation and certainly affect the minds and behavior of the people. This research is a qualitative descriptive study using a phenomenological and ethnological approach. Data collection techniques used in this study are observation, interviews, and documentation. Source of data used are primary data sources and secondary data sources, namely by using the method of territorial sampling and stratification sampling.